PENGARUH SOSIAL MEDIA INSTAGRAM TERHADAP MINAT BELI DI SELERA RESTAURANT NONGSA POINT MARINA & RESORT BATAM - Rani, Adhisty Muthia; Ibrahim, Mariaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Tourism is a sector that plays a very important role in efforts to increase foreign exchange in every country. Almost all countries in the world are competing to develop their tourist attractions. The tourism industry is seen as having very promising prospects and providing many benefits for the country. This research aims to determine the influence of Instagram social media marketing on consumer interest at Selera Restaurant Nongsa Point Marina Resort Batam. The data analysis technique used in this research is quantitative descriptive analysis, namely a research method by collecting, grouping, then arranging it so that it can be scrutinized based on relevant theories in connection with the problem being discussed and then conclusions are drawn to get the essence of the research results. namely frequency. The data collection techniques used by the author in collecting data are observation, questionnaires, and documentation. It is hoped that this research will be used as material for consideration in determining marketing strategies via Instagram social media, and can also be used as a reference for utilizing Instagram social media, to be able to introduce the Selera Restaurant profile at Nongsa Point Marina Resort Batam so that it can create advantages and be able to compete with other hotels. The research provides suggestions and hopes for the hotel to be able to increase the use of Instagram social media as a promotional medium for restaurant tastes and the profile of Nongsa Point Marina Resort. Keywords: Instagram Social Media, Restaurants, Hotels, Purchase Interest